Extrato hidroetanólico das folhas de Eugenia Aurata e de Eugenia Punicifolia (HBK) inibe a migração neutrofílica por mecanismos distintos - Costa, Mírian Feliciano [UNESP] (2015)
Myrtaceae family has been studied for its potential in regulating menstruation, pain and intestinal disorders, infertility, as well as antifungal, purgative and anticancer agent, and in addition to treat colds, cough and other respiratory ailments. Amid its members, Eugenia spp species appear to have pro and anti-inflammatory effect once examined in vivo and in vitro. Among the first cells which act on inflammation site, there are the neutrophils. They are a matter of study in the controlling of acute and chronic inflammatory processes, through elucidation of how substances act, for example, in different steps of their recruitment. Therefore, the main aim of this study was to evaluate the potential anti-inflammatory effect of hydroethanolic extract of Eugenia aurata leaves - EA and Eugenia punicifolia - EP, on neutrophil activities. We evaluated the adhesion process and cell degranulation, as well NETs (Neutrophil Extracellular Traps NETs) generation in human neutrophils. The results show that EA inhibits adhesion, while EP degranulation, and further, both inhibit the release of DNA (NET), in the absence of cytotoxic effect. These results give support to the use of these extracts in the popular medicine. Furthermore, they demonstrate a potential of both extracts for the development of phytomedicines with anti-inflammatory properties